Surprises in U.S. macroeconomic releases: Determinants of their relative impact on T-Bond futures - Dieter Hess (University of Konstanz, Center of Finance and Econometrics (CoFE), 2001)
This paper investigates the intraday response of CBOT T-bond futures prices to surprises in headline figures contained in scheduled U.S. macroeconomic news releases. While several previous studies try to find out which releases have a significant impact on prices and volatility in financial markets, considerably less effort has been devoted to the question what makes some releases important in contrast to others that seem to attract no attention at all. In order to identify the factors determining the relative importance of releases, the time series properties and the information content of the macroeconomic news flow are investigated. In particular, several types of information regarding inflation and economic strength are distinguished. The explanatory power of the type of information is tested against the alternative hypothesis that the timeliness of a release determines its impact. The results indicate that the value of the information contained in a release decreases with the number of previously released figures highlighting similar aspects. Thus, the price impact of a release decreases as the additional information contained in a release becomes smaller.
urn:nbn:de:bsz:352-opus-6579
Keywords: 330; Börsenkurs; Zinsderivat; Staatspapier; Ankündigungseffekt; Information; USA; Makroökonomischer Einfluss